BENTUK DAN PENGGUNAAN EUFEMISME DALAM HOAKS - Agus Ari Iswara; Ni Nyoman Ayu J. Sastaparamitha (RETORIKA: Jurnal Ilmu Bahasa, 2020)
This study aims to describe the form and use of euphemisms in hoax texts by meaning category. The data used is document entirely collect from the website cekfakta.com and turnbackhoax.id. The data was verified, classified and then analyzed and then was presented descriptively. The results of this study found as much as 18 forms of euphemisms, they are figurative expressions, metaphors, flippancy, remodeling, circumlocution, clippings, acronyms, abbreviations, omission, one word replacing one other word, general to specific, part to whole, hyperbole, meaning outside the statement, jargon, colloquial, borrowing, and foreign language forms. It is used in hoax for composing better speech, as if to convey facts with hyperbolic expressions, to tease or criticize others smoothly, in a political, religious, and health context.